Levels of soybean grain toast in diets for Japanese quail (Coturnix coturnix japonica) in initial phase of stance (Revista Sistemas de Producción Agroecológicos, 2012)
A research was conducted with the objective to evaluate different levels of toasted whole soybean on eggs production and egg quality on an initial laying phase. It was a total 250 birds, used in completely randomized experimental design with five treatments and five replicates and ten birds for repetition. The treatments were five diets with 0, 5, 10, 15 and 20% of grain soybean whole toasted. The experimental phase was of 84 days. The results were egg production 60, 58, 54, 57 y 54%; egg weight 10.5, 10.7, 10.5, 10.4 and 10.4; feed intake daily 24.2, 23.8, 23.9, 23.0 and 24.9; feed conversion (kg diet/kg egg 3.84, 3.83, 4.21, 3.88 and 4,43; kg diet/dozen eggs 0.484, 0.492, 0.531, 0.484 and 0.453; shell thickness 0.17, 0.16, 0.17, 0.18 and 0.17; specific gravity 1.072, 1.071, 1.073, 1.070 and 1.071; Haugh units 93.11, 91.37, 93.25, 91.73 and 92.28 for de 0, 5, 10, 15 and 20% of grain soybean whole toasted. The results showed no significant differences between treatments for production characteristics and eggshell quality. Results obtained indicate that toasted whole soybean can be including in initial laying diets of Japanese quails up to 20%.
Keywords: alternative foods; feed conversion; japanese quails; soybean grain